Angiotensin II type 1a receptor-deficient mice develop angiotensin II-induced oxidative stress and DNA damage without blood pressure increase - Zimnol, Anna; Amann, Kerstin Ute; Mandel, Philipp; Hartmann, Christina; Schupp, Nicole (American Journal of Physiology-Renal Physiology, 2017)
Hypertensive patients have an increased risk to develop kidney cancer. We have shown in vivo, that besides elevating blood pressure, angiotensin II causes DNA damage dose-dependently. Here, the role of blood pressure in the formation of DNA damage is studied. Mice lacking one of the two murine angiotensin II type 1 receptor (AT1R) subtypes, AT1aR, were equipped with osmotic minipumps, delivering angiotensin II during 28 days. Parameters of oxidative stress and DNA damage of kidneys and hearts of AT1aR-knockout mice were compared to wildtype (C57BL/6) mice receiving angiotensin II, and additionally, to wildtype (WT) mice treated with candesartan, an antagonist of both AT1R-subtypes. In WT mice, angiotensin II induced hypertension, reduced kidney function and led to a significant formation of reactive oxygen species (ROS). Furthermore, genomic damage was markedly increased in this group. All these responses to angiotensin II could be attenuated by concurrent administration of candesartan. In AT1aR-deficient mice treated with angiotensin II, systolic pressure was not increased, and renal function was not affected. However, angiotensin II still led to an increase of ROS in kidneys and hearts of these animals. Additionally, genomic damage in the form of double-strand breaks, was significantly induced in kidneys of AT1aR-deficient mice. Our results show that angiotensin II induced ROS production and DNA damage even without the presence of AT1aR and independently of blood pressure changes.
EVALuna2:25539